2023
DOI: 10.1186/s12931-023-02348-y
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 is involved in viral exacerbation of chronic obstructive pulmonary disease

Abstract: Background Our previous studies have suggested that bromodomain protein 4 (BRD4) is increased in the lung of stable chronic obstructive pulmonary disease (COPD) patients, which has been shown to be involved in inflammatory responses. We investigated its role in the viral exacerbation of COPD. Methods BRD4, interleukin (IL)-6 and IL-8 were measured in the blood and sputum of stable COPD patients and patients with viral exacerbation. Mice were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Moreover, the results exhibited a signi cant correlation between BRD4 expression and macrophage with the help of GSEV analysis, which was veri ed in the experimental emphysema mouse model. The present outcomes were also supported by a study from Duan et al (2023) [51], which reported that BRD4 expression was strongly associated with COPD viral exacerbation and also demonstrated that BRD4 expression both in the blood and in the sputum were signi cantly correlated with FEV1% predicted in stable COPD patients. Tang et al (2019) [52] reported a correlation between BRD4 expression and lung function by analyzing COPD lung tissue samples and detected an increased expression of BRD4 in the nuclei of bronchial epithelial cells by immuno-histo uorescence.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the results exhibited a signi cant correlation between BRD4 expression and macrophage with the help of GSEV analysis, which was veri ed in the experimental emphysema mouse model. The present outcomes were also supported by a study from Duan et al (2023) [51], which reported that BRD4 expression was strongly associated with COPD viral exacerbation and also demonstrated that BRD4 expression both in the blood and in the sputum were signi cantly correlated with FEV1% predicted in stable COPD patients. Tang et al (2019) [52] reported a correlation between BRD4 expression and lung function by analyzing COPD lung tissue samples and detected an increased expression of BRD4 in the nuclei of bronchial epithelial cells by immuno-histo uorescence.…”
Section: Discussionsupporting
confidence: 89%
“…This study demonstrates the efficacy of BETi in reversing established preclinical COPD. During viral exacerbation, researchers recently noticed elevated mRNA expression of BRD4 in the blood and sputum of COPD patients compared to those in a stable state [54]. Consistently, elevated BRD4 expression was found in the lungs of mice undergoing influenza infection and cigarette smoke exposure.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 78%
“…In stable or viral exacerbation of chronic obstructive pulmonary disease patients, BRD4 mRNA levels were elevated in patient blood and sputum (Duan et al, 2023). BRD4 expression was also upregulated up to sevenfolds in severe early-onset preeclampsia placenta (Liong et al, 2018).…”
Section: Bet Proteins and Inflammationmentioning
confidence: 97%
“…For example, BRD4 expression was increased in both pulmonary artery and coronary artery smooth muscle cells in rat models of pulmonary arterial hypertension (PAH) and in humans with PAH (Meloche et al., 2017). In stable or viral exacerbation of chronic obstructive pulmonary disease patients, BRD4 mRNA levels were elevated in patient blood and sputum (Duan et al., 2023). BRD4 expression was also upregulated up to sevenfolds in severe early‐onset preeclampsia placenta (Liong et al., 2018).…”
Section: Introductionmentioning
confidence: 99%